2007
DOI: 10.1111/j.1365-2621.2006.01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes in ingredient composition on the rheological properties of a biscuit industry dough

Abstract: This paper deals with the effects of changes in the amounts of ingredients added to a biscuit dough on its rheological behaviour

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…In addition, Sahi (1994) investigated that its impact also relies on upon the composition of flour along with the kind of fat and oil added. It has been found that a 30 % addition of fats repressed the starch retrogradation and provided additional plasticity on gluten network (Perego et al 2007). These perceptions affirm the finding observed by Manohar and Rao (1999), they found that the addition of fat prompted a decline in the development of gluten, henceforth the less elastic dough which is desirable in cookie making.…”
Section: Role Of Fats and Oils In Dough Rheologysupporting
confidence: 67%
“…In addition, Sahi (1994) investigated that its impact also relies on upon the composition of flour along with the kind of fat and oil added. It has been found that a 30 % addition of fats repressed the starch retrogradation and provided additional plasticity on gluten network (Perego et al 2007). These perceptions affirm the finding observed by Manohar and Rao (1999), they found that the addition of fat prompted a decline in the development of gluten, henceforth the less elastic dough which is desirable in cookie making.…”
Section: Role Of Fats and Oils In Dough Rheologysupporting
confidence: 67%
“…With respect to ash content, it was observed that the stuffed biscuit group was the one that showed the greatest variation, from 0.5 to 1.7 g/100 g. The strawberry wafer biscuit showed which are used in lower amount and lower moisture content (PEREGO et al, 2007). The long shelf life of these products allows large production and wide distribution (TYAGI et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of sucrose, the development of the gluten network is restrained because of the competition between sugar and protein for water, which might result in an incomplete hydration of gluten (Manohar & Rao, 1997;Baltsavias et al, 1999;Perego et al, 2007). Additionally, gluten polymers are highly dispersed because of sugar/water interactions and are therefore prevented from approaching each other and cross-linking.…”
Section: Technological Functions Of Sucrose In Sweetened Bakery Productsmentioning
confidence: 99%